2021
DOI: 10.3390/s21072395
|View full text |Cite
|
Sign up to set email alerts
|

Endoluminal Motion Recognition of a Magnetically-Guided Capsule Endoscope Based on Capsule-Tissue Interaction Force

Abstract: A magnetically-guided capsule endoscope, embedding flexible force sensors, is designed to measure the capsule-tissue interaction force. The flexible force sensor is composed of eight force-sensitive elements surrounding the internal permanent magnet (IPM). The control of interaction force acting on the intestinal wall can reduce patient’s discomfort and maintain the magnetic coupling between the external permanent magnet (EPM) and the IPM during capsule navigation. A flexible force sensor can achieve this cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…However, the proposed method can only be applied to limited scenarios where external forces are exerted at the tip of the endoscope alone, with no external loads on the endoscope backbone. Zhang et al 56 developed a flexible tactile sensor (shown in Figure 5) to estimate exerted forces on surrounding tissues, employing a sensor composed of piezoresistive elements placed on a flexible printed circuit. Originally developed for a tethered capsule endoscope to monitor forces exerted on the colonic mucosa, the compliance of the sensor renders it suitable for soft continuum endoscopes.…”
Section: Force-detection Techniquesmentioning
confidence: 99%
“…However, the proposed method can only be applied to limited scenarios where external forces are exerted at the tip of the endoscope alone, with no external loads on the endoscope backbone. Zhang et al 56 developed a flexible tactile sensor (shown in Figure 5) to estimate exerted forces on surrounding tissues, employing a sensor composed of piezoresistive elements placed on a flexible printed circuit. Originally developed for a tethered capsule endoscope to monitor forces exerted on the colonic mucosa, the compliance of the sensor renders it suitable for soft continuum endoscopes.…”
Section: Force-detection Techniquesmentioning
confidence: 99%
“…Due to the high dietary risk in the Chinese population, there is great demand for digestive tract endoscopy. Hence, capsule endoscopic robots have attracted extensive attention because they can easily enable comfortable examinations (122,123). In 2016, NaviCam, a magnetically driven capsule endoscopic robot, was developed by ANKON Technology Company and approved by the CFDA.…”
Section: Diagnosis and Treatment Robotsmentioning
confidence: 99%